2020
DOI: 10.1111/ijfs.14695
|View full text |Cite
|
Sign up to set email alerts
|

Effect of encapsulated Lactobacillus plantarum as probiotic on dry‐sausages during chilled storage

Abstract: The impact of free and encapsulated Lactobacillus plantarum addition on the physicochemical and microbiological properties during chilled storage (60 days) of dry-fermented sausages have been studied. Control (C) treatment was performed without probiotic incorporation, and the reformulation was comprised of L. plantarum as free cells (F) in alginate spheres (EA), in water-in-oil simple emulsion (ESM) and in water-in-oil-in-water double emulsion (EDM). After 60 days of storage, lower (P < 0.05) lipid oxidation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 31 publications
2
10
0
Order By: Relevance
“…The hardness values ranged from 10.69 to 48.04 N, springiness from 0.44 to 0.48 mm, cohesiveness from 0.35 to 0.39, and chewiness ranged from 1.47 to 8.70 (N × mm) on Days 0 and 15 of storage, respectively. Cavalheiro et al (2020) found that the addition of encapsulated Enterococcus faecium to fermented sausages led to an increase in hardness, probably due to the encapsulation by extrusion used by the authors, which may have increased the hardness of the samples.…”
Section: Texture Profilementioning
confidence: 88%
See 2 more Smart Citations
“…The hardness values ranged from 10.69 to 48.04 N, springiness from 0.44 to 0.48 mm, cohesiveness from 0.35 to 0.39, and chewiness ranged from 1.47 to 8.70 (N × mm) on Days 0 and 15 of storage, respectively. Cavalheiro et al (2020) found that the addition of encapsulated Enterococcus faecium to fermented sausages led to an increase in hardness, probably due to the encapsulation by extrusion used by the authors, which may have increased the hardness of the samples.…”
Section: Texture Profilementioning
confidence: 88%
“…Holko et al (2013) reported probiotics viability of 3 log cfu/g after 10 days of storage of fermented sausage made with non-encapsulated Bifidobacterium; thus, the product cannot be considered a probiotic product because the viability of probiotics should be 6-8 log cfu/g to be classified as a probiotic. In this context, microencapsulation techniques can be an alternative for the production of probiotic products because they can protect probiotic microorganisms against the adverse environments in the food (Cavalheiro et al, 2020). The technique consists of packaging cells in small particles using coating materials that provide a physical barrier to microbial cells (Chavarri et al, 2010).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, in W 1 /O/W 2 microparticles the aqueous polymeric outer shell is not cross-linked and as a result, these particles do not have long stability during storage and in gastrointestinal tracts. [52,58,[109][110][111][112] Ionic cross-linking was proposed to tackle this issue, in which the polymeric outer shell (W 2 ) has been mixed with an oppositely charged polymer. [51,55] Formulation C is composed of alginate as the wall material and sunflower oil loaded with probiotics as the core, and formulation D is made of alginate-shellac as the wall material and sunflower oil loaded with probiotics as the core.…”
Section: Three-layer Microparticlesmentioning
confidence: 99%
“…Another research that studied alginate encapsulated cells of Lactobacillus plantarum added in dry-fermented sausages demonstrated that, after 60 days of storage, a higher number of living bacteria (8.34 log CFU g −1 ) and a lower lipid oxidation level (0.602 mg MDA kg −1 ) were highlighted relative to free cell addition of L. plantarum in the sausages samples (8.02 log CFU g −1 , 0.625 mg MDA kg −1 ) [ 111 ].…”
Section: Nutritional Enrichmentmentioning
confidence: 99%